MODEL OF EMOTIONALLY-VALUABLE COMPONENT OF THE CONTENT OF ELEMENTARY FOREIGN LANGUAGE EDUCATION - M. N. Tatarinova (Russian State Vocational Pedagogical University, 2018)
Introduction. The component structure of the content of modern foreign language education involves the inclusion of the emotionally-valuable component (EVC), the main purpose of which is the formation of students' axiological attitude to educational material and the world around them; the acquisition of individual system of national and universal values. The process of implementing the EVC of the content of foreign language education involves the construction of its models at all levels of school foreign language education. The aim of this article is to present the invariant of the model which enables to make a selection of foreign texts of emotionally-valuable contents at the junior stage of foreign language education. Methodology and research methods. The methods of theoretical analysis (systemic-structural, organizational, functional, comparative, typological) were used in order to define basic theoretical and methodological concepts of the research. When projecting the model of the EVC of the content of foreign language education, adapted to the conditions of teaching foreign languages in elementary school, methods of designing and modelling were used. Scientific novelty and results. In the article the subcomponent structure of the EVC of the content of foreign language education is presented. It was proved that all the system subcomponents of the EVC are functional, and each of them has its own special role in elementary foreign language education. The concept of a foreign language text of emotionally-valuable contents is proposed. The choice of the form of such texts, and also the selection of an emotionally-valuable technique of work with, including conditions, means and methods, allowed us to design the invariant of the model of the EVC of the content of elementary foreign language education. Practical significance. The research materials can be useful in implementing scientifically-based selection of speech material within the discipline "Foreign Language" and the development of adequate techniques of working with texts of emotionally-valuable contents in primary school.